Business Risk, Financial Risk, and Stock Price in Determining Firm Value: Risiko Bisnis, Risiko Keuangan, dan Harga Saham dalam Menentukan Nilai Perusahaan - Amanda, Silvia; Nirwana, Nihlatul Qudus Sukma (Indonesian Journal of Law and Economics Review, 2025)
Background: Firm value is an essential indicator reflecting investors’ perceptions of company performance, and it is closely related to business risk, financial risk, and stock price. Specific Background: Prior studies show inconsistent findings regarding how these three factors relate to firm value. Knowledge Gap: Limited research examines the combined contribution of business risk, financial risk, and stock price within the same analytical model. Aim: This study aims to analyze the relationship between those variables and firm value. Results: The findings show that each variable demonstrates a measurable relationship with firm value, although the direction and strength differ across indicators. Novelty: This study offers a more integrated assessment by simultaneously incorporating three risk-related factors in one empirical model. Implications: The results contribute to financial management literature and provide insights for investors in evaluating corporate risk profiles. Highlights:• Business risk and financial risk show measurable relationships with firm value• Stock price contributes to investors’ valuation of companies• Integrated analysis strengthens the understanding of corporate risk dynamics Keywords: Business Risk, Financial Risk, Stock Price, Firm Value, Corporate Finance